Globalization and Discourse on Terror: Hari Kunzru's Transmission as post 9/11 Fiction. - Perveen, Ayesha; Anwar, Nadia (Journal of Social Sciences & Humanities (1994-7046))
The study analyzes Hari Kunzru's (b. 1969) novel Transmission (2004) as a post 9/11 text. Although there are no direct references to the events of 9/11, the novel is analogous to the counter-discourses against post 9/11 popular discourses on terror. The theoretical framework of the study is based on Baudrillard's critique of 9/11 as presented in his 2001 essay "The Spirit of Terrorism" which contends that 9/11 attacks were symbolic of a reaction against globalization and its negative impact on the third world. The terrorists retaliated against global neo-imperialism and ironically used the same means of globalization in the form of modern technology to wage a war against the selfproclaimed superpower, the USA. Since both Arjun Mehta and Leela Zahir, the protagonists of the novel, are labelled as terrorists, the post 9/11 discourse on terror as presented by the West and its counter-discourse as presented by the Western 'other' will be examined at length through a close reading of the text. Arjun Mehta, a budding computer programmer, struggles to eradicate his poverty for a secure future but is marked as a terrorist that makes him end up as a fugitive. Similarly, Leela Zahir, a promising actress with the prospects of touching the pinnacles of fame, is devastated because of being associated with computer generated virus. The novel is counter-discursive to the creation of the tag 'terrorist' through exposing the role of unequal distribution of wealth, opportunities and security in a globalized world in the making of terrorists (real or simulated), hence corresponding to 9/11 discourses. The paper concludes that the novel is a critique of globalization as a source of terror in the new millennium through the use of media and technology.